Adaptation Experiences of Family Caregivers of Children with Congenital Birth Defects in the Accra Metropolis - Ahiable, D.Y. (University of Ghana, 2020)
Literature evidence indicate that, taking care of children with congenital birth defects can be a difficult task to the caregivers, who most of the time are mothers, fathers or dedicated family relations of the children. The caregiver role is seen to be associated with a lot of hassles, which may predispose the prospective caregivers to psychological as well as physical ill-health situations. However, only few works have been done on the experiences of caregivers of children with condition-specific defects in Ghana. This work therefore explored the adaptation experiences of family caregivers of children with congenital birth defects in the Accra Metropolis, using the transactional stress model by Lazarus (1991), as the guiding framework and adopting five objectives suggested by its constructs. The study adopted a qualitative descriptive approach. Data was collected through in-depth face to face interview sessions with thirteen (13) purposively selected participants, using the Dzorwulu special school as the setting. The interviews were audio-taped, transcribed verbatim and analysed using thematic content analysis. In all, seven themes were identified as follows; Life events of family caregivers, appraisals of these events, resources and support available to them, health consequences they face, their coping strategies, adaptation measures and their religiosity. In conclusion the study found out that; family caregivers consider having a child with congenital birth defects as a major life event, face a lot of challenges in caring for them with less resources and support. But the effect on their health was minimal as they adopted a number of coping and adaptation strategies. Meanwhile, religiosity appeared to have given them respite on issues that went beyond their imagination. Specific policies are therefore required to support caregivers of children with congenital defects to enhance their role.
MPhil. Nursing
Keywords: Congenital birth defects; Children; Caregiver role; Ghana